HUBUNGAN KONSUMSI MINUMAN BERPEMANIS DENGAN RISIKO OBESITAS PADA REMAJA DI SMA NEGERI 53 JAKARTA - Nourmayansa Vidya Anggraini; Lestarie Luhur (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2025)
Sugar-sweetened beverages take second and third place in terms of beverage consumption in Indonesia. Consumption of simple sugars has a 5.7 times risk of obesity. The results of a preliminary study conducted on 244 class X students at SMAN 53 Jakarta, the prevalence of overweight status in students was 24.1% with 18.4% of them experiencing overweight. This study aims to determine the relationship between sugar-sweetened beverage consumption and the risk of obesity in adolescents at SMA Negeri 53 Jakarta. The study was conducted on 221 respondents who were selected according to the criteria determined through purposive sampling technique. Obesity risk data was obtained through measurement of BMI, while consumption of sugar-sweetened beverages was measured based on the frequency of consumption of sweetened beverages which was converted into sufficient sugar intake (50g/day) through Semi Quantitative Food Frequency. The results of the chi square test analysis showed a relationship between consumption of sugar-sweetened beverages and the risk of obesity in adolescents at SMA Negeri 53 Jakarta. Adolescent students and schools are expected to contribute to limiting and controlling the consumption of sugary drinks as an effort to reduce the incidence of obesity.